Tax revenue performance and vulnerability in developing countries - Morrissey, Oliver; Haldenwang, Christian von; Schiller, Armin von; Ivanyna, Maksym; Bordon, Ingo (Taylor & Francis, 2016)
This paper addresses vulnerability of revenue to external shocks using export composition to capture economic structure and differentiating countries according to income levels, resource endowments and political regimes. This gives a richer characterization than previous studies. Lower income countries are vulnerable to shocks, especially in terms of trade (associated with the greatest revenue loss): democratic regimes seem to be less vulnerable to revenue losses due to shocks than non-democracies whereas revenue in resource rich is more vulnerable to shocks (except natural disasters) than non-resource rich countries. We find a negative relationship between manufacturing exports and revenue in lower income countries.